(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Juvenile granulosa cell tumors (JGCTs) are rare sex cord stromal tumors diagnosed mainly in premenarchal girls and women younger than 30 years. Case presentation: A 19-year-old primigravida at 36 weeks of gestation presented to the labor ward with complaints of generalized abdominal pain, headaches, and reduced fetal movements for two days. Ultrasound revealed a left-sided 15.7 by 15 cm large cyst and a solid mass of increased vascularity with maternal ascites. The biophysical profile of the fetus was 4/8 (no movement or tone but the presence of respiration and amniotic fluid). An emergency exploratory laparotomy was performed, and intraoperative findings revealed a massive torsed right ovary with a ruptured ovarian mass with grossly edematous and necrosed fallopian tubes. Following a safe cesarean section delivery of the fetus, a right salpingo- oophorectomy with cystectomy was performed. The histopathological results confirmed the diagnosis of JGCT FIGO stage IC2. Postoperatively, the patient was treated with six sessions of chemotherapy (cisplatin and paclitaxel). Post-chemotherapy magnetic resonance imaging showed normal abdominal viscera with minimal free fluid in the posterior cul de sac and a normal left ovary. Inhibin B levels dropped to 3.17, and the patient is on follow-up for the next 5 years with repeated tumor marker testing and computed tomography scans. Conclusion: JGCT is a very uncommon pregnancy tumor, and aggressive treatment is necessary for advanced-stage tumors such as the one in this case to prevent recurrence or even death.